2018
DOI: 10.1530/erc-18-0068
|View full text |Cite
|
Sign up to set email alerts
|

Splicing dysregulation as a driver of breast cancer

Abstract: Breast cancer is known to be a heterogeneous disease driven by a large repertoire of molecular abnormalities, which contribute to its diverse clinical behaviour. Despite the success of targeted therapy approaches for breast cancer patient management, there is still a lack of the molecular understanding of aggressive forms of the disease and clinical management of these patients remains difficult. The advent of high-throughput sequencing technologies has paved the way for a more complete understanding of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 93 publications
1
24
0
1
Order By: Relevance
“…Decades of research have revealed an array of dynamic regulatory networks that control each phase of gene expression (48,52,53). When these mechanisms fail, it can result in the development of numerous diseases, including cancer (51,(54)(55)(56). Understanding how different signaling events directly impact the initial phases of gene expression will provide new insight into the mechanisms of disease and identify new strategies for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Decades of research have revealed an array of dynamic regulatory networks that control each phase of gene expression (48,52,53). When these mechanisms fail, it can result in the development of numerous diseases, including cancer (51,(54)(55)(56). Understanding how different signaling events directly impact the initial phases of gene expression will provide new insight into the mechanisms of disease and identify new strategies for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Note that 95% of pre-mRNAs are alternatively spliced in humans,6 leading to at least 100,000 distinct proteins despite only 20,000 protein-coding genes 7. Once disorders, abnormal protein subtype will be formed and deregulate multiple biological processes, such as cell proliferation, differentiation, apoptosis, cycle, metabolism, invasion, migration and angiogenesis,8 and has been considered to be involved in the development of many kinds of tumors, including ovarian cancer,9 lung cancer,10 osteosarcoma,11 gastric cancer12 and breast cancer,13 and so on. In recent years, studies have found that PUF60, a splicing factor, is involved in the progression of several various kinds of tumors 14.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a cohort study demonstrated that SF3B1 mutations occur in >20% of patients with uveal melanoma ( 39 ). SFs are also involved in the biological processes of BRCA, such as tumorigenesis, growth, infiltration and metastasis, and are thus involved in prognosis ( 9 , 12 , 40 42 ). SFs and AS have been found in the immune-evasion pathway of tumors ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of AS in BRCA has recently been investigated, with studies analyzing certain AS events in breast cancer; these studies have demonstrated the potential for specific AS events to classify and diagnose cancer (9,10). Tien et al (11) demonstrated that the mutation of cyclin-dependent kinase 12, which disrupts DNA repair, affected a DNAJB6 isoform and the DNA damage response activator by regulating last-exon splicing; thereby causing tumorigenesis and invasion.…”
Section: Introductionmentioning
confidence: 99%